Redefining health care : creating value-based competition on results - Porter, Michael E., 1947- (Harvard Business School Press, 2006)
"Health care in the United States and other nations is on a collision course with patient needs and economic reality. Rising costs, mounting quality problems, and increasing numbers of citizens without health insurance are unacceptable--and unsustainable. In Redefining Health Care, Michael E. Porter and Elizabeth Olmstead Teisberg set forth a new vision of the health care system in which every actor is focused on improving value, as measured by health outcomes per dollar expended. The authors prescribe a powerful and actionable agenda for change"--P. [2] of cover.